1994
DOI: 10.1016/0014-5793(94)80455-9
|View full text |Cite
|
Sign up to set email alerts
|

PRE3, highly homologous to the human major histocompatibility complex‐linked LMP2 (RING12) gene, codes for a yeast proteasome subunit necessary for the peptidylglutamyl‐peptide hydrolyzing activity

Abstract: 20S proteasomes are multifunctional proteinase complexes ubiquitous in eucaryotes. We have cloned the yeast PRE3 gene by complementation of the pre3‐2 mutation, which leads to a defect in the peptidylglutamyl‐peptide hydrolyzing activity of the 20S proteasome. The PRE3 gene, a β‐type member of the proteasomal gene family, is essential for cellular life and codes for a 193‐amino acid proteasomal subunit with a predicted molecular mass of 21.2 kDa. The Pre3 protein shows striking homology to the human proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…Yeast mutants deficient in proteasomal PGPH activity are mutated in the genes PRE3 and PRE4, the yeast homologues of delta and N3, respectively (12,13,38). Delta has the structural features of enzymatically active subunits while N3 does not (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast mutants deficient in proteasomal PGPH activity are mutated in the genes PRE3 and PRE4, the yeast homologues of delta and N3, respectively (12,13,38). Delta has the structural features of enzymatically active subunits while N3 does not (7).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, 7 different types of ␤ subunits have been detected in yeast cells and 10 in various mammalian cells (9). Analysis of yeast mutants defective in the chymotryptic or peptidylglutamyl peptide hydrolyzing (PGPH) activities of the proteasome has shown that in these cases mutations in two different ␤ subunits were responsible for a single type of activity (10)(11)(12)(13). Apparently, cooperation between two different ␤ subunits is necessary for expression of a single activity and location of these subunits within the proteasome complex cannot be fortuitous.…”
mentioning
confidence: 99%
“…In eukaryotes, however, prosequences are longer and more heterogeneous 123,124 and only three subunits (PRE2, PRE3, and PUB1) of the seven distinct β-subunits of the yeast proteasome are processed and become catalytically active. [107][108][109]125 Similarly, X, Y, and Z β-subunits of mammalian proteasome are catalytically active. The processing event appears to be autocatalytic as in other Ntn hydrolases 117 and coupled to proteasome assembly.…”
Section: B 20s and 26s Proteasome: Converging Points Of Ubiquitinatementioning
confidence: 99%
“…The "trypsin-like" activity cleaves substrates after basic residues and the "peptidyl-glutamyl peptide hydrolytic" (PGPH) or "caspase-like" activity cleaves after acidic residues (13,14). These primary hydrolytic activities have been linked through mutagenesis and inhibitor studies to three catalytically active ␤ subunits: ␤1, ␤2, and ␤5 (15). These studies have assigned the chymotryptic activity to ␤5, the tryptic activity to ␤2, and the PGPH activity to ␤1 (16).…”
mentioning
confidence: 99%